Highly luminescent perovskite quantum dots for light-emitting devices: photopatternable perovskite quantum dot–polymer nanocomposites. Issue 42 (11th October 2022) - Sung, Cheng-Han; Huang, Shi-Da; Kumar, Gautham; Lin, Wen-Chi; Lin, Chien-Chung; Kuo, Hao-Chung; Chen, Fang-Chung
Abstract : Photopatternable perovskite quantum dot–polymer composites with feature sizes as small as 3.86 μm are prepared for light-emitting applications. Abstract : In this study we synthesize organic–inorganic hybrid perovskite quantum dots (PeQDs) having a high photoluminescence quantum yield (PLQY = 98%) for light-emitting applications. The luminescence peak of the FAPbBr3 (FA + : formamidinium) PeQDs in solution is located at 527 nm; its CIE 1931 color coordinates are (0.169, 0.760), very close to the BT.2020 standard (0.170, 0.797). After mixing the PeQDs with polydimethylsiloxane, the mixture behaves as a color-conversion layer (CCL) for quantum-dot light emitting diodes (LEDs), achieving a high power efficiency (129.4 lm W −1 ). Because PeQDs readily decompose in most polar solvents, we blend ours with polyvinylcinnamate (PVCN), which is readily soluble in toluene, to formulate photopatternable thin films. The resulting photopatternable perovskite quantum dot–polymer nanocomposites (PQD–PNCs) can be patterned using UV light to achieve feature sizes as small as 3.86 μm. The highest PLQY of the PQD–PNC film (47%) is greater than that of the neat QD film (40%), while the stability of the PQD–PNC is also better than that of the neat film, presumably because of the hydrophobic nature of PVCN. These results suggest the high potential of PQD–PNCs as effective CCLs for future micro-LEDs.